The impact of populism on central bank communication: Analyzing theoretical developments and the case of Hungary - Maxence Follot (The European Journal of Comparative Economics)
This study examines the impact of populism on central bank communication, with a focus on theoretical developments and the specific case of Hungary. Populism, characterised by the opposition between ‘the pure people’ and ‘the corrupt elite’, challenges traditional institutions, including central banks, which are seen as part of the elite due to their unelected technocratic leadership. The rise of populism has led to increased scrutiny and pressure on central banks, which have been forced to adapt their communication strategies in order to maintain credibility and public trust. The analysis explores how central banks are shifting their communication to defend their reputation in response to populist pressures, moving away from traditional roles and toward a focus on predictability and public engagement.